GO-MUTRA : BOON TO HUMAN BEINGS (International Journal of Ayurveda and Pharma Research, 2016)
Cow is considered as mother in Indian tradition. Go-mutra (cow urine) is one of the ingredient of Panchgawya, extensively used in Ayurved for treatment of many diseases. Go-mutra (cow urine) is used in treatment since time immemorial as cited in Atharvaveda, Carak Samhita, Sushrut Samhita, Vagbhatt, Bhavprakash etc. Go-mutra (cow urine) is a divine medicine considered as Medhya (intellect promoting) and is used for treatment of various diseases. Go-mutra (cow urine) as a single medicine is capable of curing diseases like Kandu (pruritis), Kilas (skin disorder), Shool (pain), Gulm, Atisar (diarrhea), Vaatrog, Kaas (cough), Kusth (skin disorders), Krimi (worm infestation), Pandu (anaemia) and Udarrog (abdominal distention). Go-mutra (cow urine) is extensively used in various Ayurvedic preparations like Go-mutra Haritaki, Sanjeevani Vati etc.Recent studies has proved efficacy of Go-mutra (cow urine) in diseases like diabetes, blood pressure, cancer etc. Various chemical substances like Aurum hydroxide etc. and vitamins present in cow urine explain its medicinal properties. Due to such vast utility of Go-mutra (cow urine), its synonym is Brahmambu & thus, it is considered as elixir of life by Acharays of Ayurveda. Go-mutra (cow urine) is the most effective natural remedy & safest method of treatment bestowed upon us by mother-nature. This paper will put forward the constituents of Go-mutra and its medicinal importance.